The Experiences of White Male Counsellors Who Work with First Nations Clients - Smith, D. Bruce; Morrissette, Patrick J. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper describes a qualitative study that investigated the experiences of White male counsellors who work with First Nations clients. Five experienced counsellors participated in individual, tape-recorded interviews, during which they described their experiences, yielding written protocols that were thematically analyzed. Results from this study revealed five predominant themes that included the following: (a) encountering difference, (b) establishing relationships, (c) a willingness to learn, (d) evolving professional identities, and (e) impact on self-awareness. Findings and implications for White counsellors and counsellor educators are included.